Japanese multicenter estimation of wallflex duodenal stent for unresectable malignant gastric outlet obstruction. Issue 1 (26th April 2012) - Sasaki, Takashi; Isayama, Hiroyuki; Maetani, Iruru; Nakai, Yousuke; Kogure, Hirofumi; Kawakubo, Kazumichi; Mizuno, Suguru; Yagioka, Hiroshi; Matsubara, Saburo; Ito, Yukiko; Yamamoto, Natsuyo; Sasahira, Naoki; et al.
<x xml:space="preserve">Abstract</x> Aim This retrospective study estimated the efficacy and safety of the WallFlex duodenal stent for malignant gastric outlet obstruction (GOO) in Japan. Methods Forty‐two consecutive patients with symptomatic malignant GOO were treated using WallFlex duodenal stents between January 2010 and October 2010. Results The technical and clinical success rates were 100% and 83.3%, respectively.The median gastric outlet obstruction scoring system increased significantly, from 0 to 2, after stent placement (P < 0.01).The median survival time was 3.3 months (95% confidence interval (CI), 1.8–6.0 months), and the median eating period was 3.0 months (95% CI, 1.1–4.3 months). Re‐intervention was required in 11 patients (26.2%). The complication rate was 26.2%. The major complication was stent occlusion (23.8%) by tumor ingrowth, which occurred in nine (21.4%) patients, and tumor overgrowth, which occurred in one (2.4%) patient. Stentmigration, perforation, and food impaction without stent occlusion were not observed.The median survival time of the patients with stent occlusion was 11.7 months (95% CI, 2.2 months – not reached), and the median stent patency of these patients was 4.0 months (95% CI, 0.8–4.7 months).These patients were successfully treated with additional stent insertion using a stent‐in‐stent procedure. Conclusion Duodenal stent placement using a WallFlex duodenal stent was safe and effective for managing malignant GOO.This stent is an uncovered metallic stent, and the major problem was stent occlusion due to tumor ingrowth. However, the occluded stent could be corrected by inserting an additional duodenal stent.